2015
DOI: 10.1080/03004430.2015.1016506
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural outcomes of four-year-old children prenatally exposed to methadone or buprenorphine: a test of three risk models

Abstract: It is still under debate whether the reported effects of opioid maintenance therapy (OMT) on child behavior are a direct effect of prenatal exposure, or whether other factors are involved. This prospective cohort study investigated three models; the teratogenic risk model, the maternal risk model, and a combined risk model in a group of 35 children (M = 52.20 months, SD = 1.69) prenatally exposed to OMT. Results revealed support for the maternal risk model and the combined model, with the combined model predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The Reynell Developmental Language Scales were used in two studies (93 methadone‐exposed vs 76 unexposed children) at 3 years and at 4 years; both reported reduced performance in expressive and comprehensive language. Of the seven studies assessing behaviour, six reported more behavioural problems in methadone‐exposed children than in unexposed children . Details of all studies reporting childhood neurodevelopmental outcome after prenatal methadone exposure are summarized in Table SII (online supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The Reynell Developmental Language Scales were used in two studies (93 methadone‐exposed vs 76 unexposed children) at 3 years and at 4 years; both reported reduced performance in expressive and comprehensive language. Of the seven studies assessing behaviour, six reported more behavioural problems in methadone‐exposed children than in unexposed children . Details of all studies reporting childhood neurodevelopmental outcome after prenatal methadone exposure are summarized in Table SII (online supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Results supported both the maternal risk and combined models, with the combined model being most predictive of a child's developing internalizing and externalizing behavior problems. 80 Many more factors beyond the scope of this review (such as maternal emotion regulation, attachment behaviors, parenting stress, and maternal and parental parenting behavior) may also play a role in childhood developmental outcomes and are difficult to detangle from risk of drug use. Studies suggest an interaction between stress and substance use.…”
Section: Environment and Nas Outcomesmentioning
confidence: 99%
“…They also underline the differences between the mothers of the two groups concerning education and employment rates and other possible factors (such as maternal use of tobacco, other legal and illegal drugs in pregnancy, family situation) which could have influenced the results. Konijnenberg test out three risk models in her latest publication and the findings suggest that behaviour problems of children of women in OMT may not be a direct exposure effect [135]. She writes that this underscores the importance of taking multiple factors into consideration when studying the effects of prenatal OMT exposure on child behaviour.…”
Section: Omt In Pregnancy -Possible Long-term Effects For the Childmentioning
confidence: 99%